Brønsted‐Acid‐Catalyzed One‐Pot Synthesis of β, β‐Diaryl Esters: Direct Regioselective Approach to Diverse Arrays of 3‐Aryl‐1‐indanone Cores. Issue 2 (10th November 2022) - Sharma, Pragya; Taneja, Neha; Singh, Sanjay; Hazra, Chinmoy K.
Abstract: A three‐component, solvent‐dependent, Brønsted‐acid‐catalyzed reaction of benzaldehydes, silyl enolates and arene nucleophiles has been developed for the synthesis of potential drug candidate 3‐aryl‐1‐indanones. This reaction features the formation of three C−C bonds, high regioselectivity in a one‐pot strategy, broad substrate generality, facile scalability (1.04 g ), high functional group tolerance and viable substrates. The β‐ O ‐silyl ethers generated in‐situ from the Mukaiyama aldol reaction were subjected to acid‐catalyzed benzylic arylation with strong as well as weak nucleophiles, and the resultant β, β‐diaryl esters can undergo a third C−C bond formation with excellent regioselectivity through intramolecular cyclization to afford the indanone products in the same pot. Detailed mechanistic insight leads to a feasible reaction pathway. This transformation opens up a practical and adaptable approach to producing a variety of synthetically valuable transformations and enable the synthesis of medicinally valuable ( R )‐tolterodine and (+)‐indatraline. Abstract : Three‐component, solvent‐dependent, Brønsted‐acid‐catalyzed reaction of benzaldehydes, silyl enolates and arene nucleophiles has been developed for the synthesis of potential drug candidate 3‐aryl‐1‐indanones. This reaction features the formation of three C−C bonds, high regioselectivity in a one‐pot strategy, broad substrate generality, facile scalability, high functional group tolerance and viable substrates.